Access to justice in Colombia must materialize a true social rule of law - Gómez Lozano, María Margarita (DIXI, 2024)
The article aims to analyze access to justice as an institution that has been subject to diverse interpretations, complicating its definition in terms of scope, commitments, and limitations. This is because it represents the realization and balancing of human rights, as well as the implementation of the programs and projects on which the Colombian State was founded. Therefore, the position of the Constitutional Court is used to explain the process of access to justice as an institution, given that compliance with the law is manifested not only through human rights but also by achieving goals and values that strengthen the government. Many publications have questioned its scope, meaning, and limitations. To address this, the decisions of the Colombian Constitutional Court are considered regarding the establishment of a comprehensive system of judicial adjudication by judges, the nature of law and its justice, and actions taken according to its position as a fundamental legal authority. Among its partisan guarantees, the Court has many responsibilities to ensure compliance with the constraints that must be taken into account. Likewise, its contribution regarding the concept of constitution and the determination of the organizational structure, particularly related to the jurisdiction established by Colombian law and the use of other methods of public justice administration, will be explained. The Inter-American Court of Human Rights has become the primary normative source for justice—and even customary law—to elevate access to justice to the level of a fundamental right. The jurisprudence of this corporation has recognized it as a fundamental right, placing it within Articles 8 and 25, in relation to Article 1.1 of the Convention. Furthermore, it has gradually enriched its content, expanding it beyond the criminal field and applying it to all areas, considering it as the “Right of Rights.”